HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP PERILAKU PENCEGAHAN DEMAM BERDARAH DENGUE PADA MASYARAKAT DI WILAYAH KERJA PUSKESMAS AMURANG TIMUR - Sintikhe Ribka; Jilly Toar; Christian Bertom Pajung (JURNAL ILMIAH KESEHATAN MANADO, 2024)
In 2023, Puskesmas Amurang recorded 32 cases of dengue fever, but from the beginning of 2024 until June, the number of cases increased to 63, with 1 death due to dengue fever. However, the increase in the incidence of dengue fever indicates that there are issues in the process of optimizing the implementation of dengue prevention efforts. The aim of this study is to determine the relationship between knowledge and attitudes towards dengue fever prevention behaviors in the community within the working area of the Amurang Timur Health Center. The method used in this study is a quantitative approach with a cross-sectional design. The sample used in this study consisted of 98 respondents. The data collection technique used primary and secondary data. The research results obtained indicate that there is a relationship between knowledge and DBD prevention behavior in the community within the working area of Puskesmas Amurang Timur, with a p-value of 0.000 < 0.05, and there is a relationship between attitude and DBD prevention behavior in the community within the working area of Puskesmas Amurang Timur, with a p-value of 0.001 < 0.05.